Pulmonary function and maximal transrespiratory pressures in ankylosing spondylitis. Issue 8 (August 1989) - Vanderschueren, D; Decramer, M; Van den Daele, P; Dequeker, J
Abstract : Clinical measurements and pulmonary functions, including maximal transrespiratory pressures, were studied in 30 patients (age 43 (SD 10) years) with ankylosing spondylitis. Vital capacity (VC) was slightly reduced to 79 (16)% and forced expiratory volume in one second (FEV1) was similarly reduced to 82 (20)% such that the average FEV1/VC ratio was 77.8 (6.65). Total lung capacity was slightly reduced to 85 (13)%. Transfer factor of the lung for carbon monoxide (TLCO) averaged 88 (17)% and TLCO per unit lung volume was 114 (26)%. Reductions in lung volumes correlated well with clinical measurements. Both maximal expiratory pressures (PEmax) and inspiratory pressures (PImax) were clearly reduced to 56 (17)% and 76 (28)% respectively. This suggests that spirometrically determined volumes were better preserved than respiratory muscle strength in ankylosing spondylitis. It is speculated that the reduction in respiratory muscle strength may be due to intercostal muscle atrophy.